Penerapan Model Probing Prompting Untuk Meningkatkan Keterampilan Berkomunikasi Siswa - Uswatun Khasanah (Academia Publication, 2022)
This study aims to: 1) determine students' communication skills before applying the Probing Prompting Learning Model in Civics lessons for fifth grade students, 2) determine students' communication skills after applying the Probing Prompting Learning Model in Civics lessons. fifth grade students, 3) improve students' communication skills in Civics material after applying the Probing Prompting learning method for fifth grade students. This study uses a Classroom Action Research approach. The data collection techniques in this study are observation and tests. The results showed that: 1) Through the Probing Prompting learning model there was an increase in the communication skills of fifth grade students at SD Negeri 101390 Batang Pane 1 in Civics learning. 2) Students' communication skills were obtained through the application of the Probing Prompting learning model, namely the average score of students' communication skills in the first cycle was 76.88 and increased by 94.75 in the second cycle. The Probing Prompting learning model has been implemented according to the learning scenario in class V at SD Negeri 101390 Batang Pane 1.